Paradox of Life, Liberty and the Pursuit of Happiness in Guns N’ Roses “Civil War” - Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
The United States of America has long been known as the pioneer of freedom and democracy. The country promotes the idea of acquiring self-fulfillment without interfering others.  Man can have his freedom upon life, liberty and the pursuit of happiness given to him ever since he was born. The long history of the United States of America recorded events and tumults testing the loftiness of American Dream. One of the American rock bands portraying the aforementioned situation is Guns N’ Roses. The lyric of “Civil War” clearly describes the paradox of life, liberty and the pursuit of happiness. Protest against war was increasing. Thus, the waves of strike and demonstration occurred as critics toward Government policy. At this point, rock bands also have important roles in accommodating people’s hopes and wishes. By using several elements of poetry, an argumentative analysis is developed and elaborated in order to reveal the attitude of people regarding government policy on war..                             Keywords: Paradox; War, Government policy; Guns N’ Roses;